2020
DOI: 10.1515/reveh-2020-0041
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic lateral sclerosis, occupational exposure to extremely low frequency magnetic fields and electric shocks: a systematic review and meta-analysis

Abstract: Exposure to extremely low frequency magnetic fields (ELF-MF) and electric shocks occurs in many workplaces and occupations but it is unclear whether any of these exposures cause Amyotrophic lateral sclerosis (ALS). The aim of this systematic review and meta-analysis is to explore whether occupational exposure to ELF-MF and/or electric shocks are risk factor for ALS. We searched PubMed, Embase, and Web of Science databases up to the end of 2019. Pooled risk estimates were calculated using random-effects meta-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…We also did not find that occupational exposure to electromagnetic radiation increases ALS risk, which could be due to the low number of individuals reporting this exposure in our cohort, most of whom were health care workers. A recent meta-analysis suggests that electromagnetic radiation exposure slightly increases ALS risk (Jalilian et al 2021 ), although reports included in the meta-analysis were mixed, indicating that the risk is not uniform across all studies.…”
Section: Discussionmentioning
confidence: 99%
“…We also did not find that occupational exposure to electromagnetic radiation increases ALS risk, which could be due to the low number of individuals reporting this exposure in our cohort, most of whom were health care workers. A recent meta-analysis suggests that electromagnetic radiation exposure slightly increases ALS risk (Jalilian et al 2021 ), although reports included in the meta-analysis were mixed, indicating that the risk is not uniform across all studies.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it seems most plausible that the results we found are coincidental, and not signs of a causal link. Recent reviews and meta-analyses have come to conflicting conclusions, where some conclude that ALS is associated with occupational exposure to magnetic fields, but not to electric shock [ 35 , 36 ] whereas another highlights a history of electric shock as a risk factor for ALS [ 37 ]. Our data set did not include enough cases to shed further light on this question.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from New Zealand reported an association between occupational exposure to electric shocks and ALS but did not show associations with exposure to work-related ELF-MF [Chen et al, 2021]. A more recent meta-analysis reported a weak association between occupational exposure to ELF-MF and the risk of ALS and reported no association between occupational exposure to electric shocks and risk of ALS; however, there was substantial heterogeneity in the results of the included studies [Jalilian et al, 2020].…”
Section: Introductionmentioning
confidence: 97%